2015
DOI: 10.1007/s11356-015-5141-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative responses of river biofilms at the community level to common organic solvent and herbicide exposure

Abstract: Residual pesticides applied to crops migrate from agricultural lands to surface and ground waters. River biofilms are the first aquatic non-target organisms which interact with pesticides. Therefore, ecotoxicological experiments were performed at laboratory scale under controlled conditions to investigate the community-level responses of river biofilms to a chloroacetanilide herbicide (alachlor) and organic solvent (methanol) exposure through the development referenced to control. Triplicate rotating annular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…While pesticides entering surface waters may adsorb to periphyton, pesticides that do not partition into periphyton can also alter its nutritional value. This has been observed in cases where herbicide exposure has led to a decrease in periphyton biomass (Debenest et al, 2009; Paule et al, 2016), thereby limiting the food resources available to primary consumers. Pesticide exposure has also been shown to cause a shift in the composition of periphyton microorganisms toward species which are more tolerant of pesticide exposure (Schmitt‐Jansen & Altenburger, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…While pesticides entering surface waters may adsorb to periphyton, pesticides that do not partition into periphyton can also alter its nutritional value. This has been observed in cases where herbicide exposure has led to a decrease in periphyton biomass (Debenest et al, 2009; Paule et al, 2016), thereby limiting the food resources available to primary consumers. Pesticide exposure has also been shown to cause a shift in the composition of periphyton microorganisms toward species which are more tolerant of pesticide exposure (Schmitt‐Jansen & Altenburger, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Alachlor effect was mainly limited to biomass reduction only for younger biofilms (less than 2 weeks of age) without apparent changes in the ecological succession trajectories of bacterial and diatom communities and suggested that carbon utilization spectra of the biofilm are not damaged resulting. By using smaller triplicate rotating annular bioreactors, alachlor at 1 or 10 μg L −1 was applied through early stages of biofilm development, from time 0 to 5 weeks (Paule et al 2015). The results suggested that the concentration-dependent effect of alachlor mainly remains limitedto biomass andgrowth inhibition without apparent changes of ecological succession trajectories and functional characteristics.…”
Section: Pollutants and Microbesmentioning
confidence: 98%
“…This study showed that an insecticide such as fipronil may pose hazards to freshwater primary producers and decomposers. It has been demonstrated that herbicides (Paule et al, 2016;Chaumet et al, 2019;Dorigo et al, 2010) and their mixtures (Ham et al, 2014;Morin et al, 2012;Pesce et al, 2011) affect the microbial and photosynthetic fractions of the periphyton. However, as far as we know there is no information on the ecotoxicity effect of insecticides on biofilms.…”
Section: Effect Of Fipronil On Periphytonmentioning
confidence: 99%